Inside Back Cover: Rational design for thermochromic luminescence in amorphous polystyrene films with bis‐o‐carborane‐substituted enhanced conjugated molecule having aggregation‐induced luminochromism. Issue 5 (22nd October 2021) - Wada, Keisuke; Hashimoto, Kazushi; Ochi, Junki; Tanaka, Kazuo; Chujo, Yoshiki
Abstract : We designed and synthesized bis‐ o ‐carborane‐modified luminophores for obtaining stimuli‐responsive luminochromism in the solid state. The compounds show intense emission in condensed and crystalline states by suppressing aggregation‐caused quenching. Especially, we fabricated dye‐loaded polystyrene films and successfully observed thermochromic luminescence. Our materials are expected to be a versatile scaffold for developing film‐type sensors. ( Aggregate . 2021;2:e93 )